Kegiatan Fun Luhgawi Berbasis Metode Belajar Ibnu Sina - Atiqurrahman, Hamdi; Mufidah, Nuril (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2023)
The purpose of this study is to describe how the application of ibnu sina's learning method in fun lughawi activities.  This article uses descriptive qualitative research method (libary research). The data sources used come from books, journals, scientific works, and so on. The subject of this research is students who take part in fun lughawi activities in 2022-2023. The results of this study are among the 7 methods of learning ibnu sina (talqin method, demonstration, exemplary and habit, discussion, apprenticeship, giving assignments, tarhib and targhib.) There are 3 methods that are applied; 1. Talqin method, musrif reads the vocabulary first and students listen and then mention it too so that students memorize the vocabulary. 2. Demonstration method, students are required to use the vocabulary that has been given by musrif beforehand. 3. Tarhib and Targhib method, this method is in the form of giving rewards and punishments, if students participate in fun lughawi activities and perform well then they will be given a prize, and if they do not participate in these activities they will be subject to punishment such as writing wirdul lathif.